Microbial spore genetic marker technology, a potential technology for traditional Chinese medicine traceability system - Dazhong Zhao; Zunzhe Tian; Jing Cai; Juan He (BMC, 2022)
Abstract Traditional Chinese medicine (TCM) has a long history, rich clinical experience, and unique advantages in the prevention and treatment of diseases. The quality and safety of Chinese medicinal materials (CMMs) directly affect the clinical efficacy and development of the TCM industry. However, confused provenance, counterfeiting and adulteration of CMMs hinder the acceptance of its therapeutic benefits in modern society. Therefore, the establishment and improvement of a TCM traceability system would be conducive to the transparency of the CMMs production, distribution, and circulation, thereby improving drug safety and promoting industry development. This review discusses the challenges faced in the development of TCM traceability system, the technologies currently available for tracing CMMs, and the potential application of Barcoded Microbial Spores (BMS) to improve CMMs origin traceability and TCM traceability systems.